Bentuk-Bentuk Perubahan Pertukaran dalam Perkawinan Bajapuik - M, Maihasni; Sumarti, Titik; Sri Wahyuni, Ekawati (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2010)
The objective of this paper to identified and analysis of types that use in bajapuik marriage as a basic of exchange and factors that its influence. The reseach is a qualitative aproach with using multi method approaches in order to explain the phenomena proposed.The result of the study showed that types exchange in bajapuik marriage involved; 1) uang jemputan; 2) uang hilang; 3) uang selo; 4) uang tungkatan. All of types that are exchenged in bajapuik marriage in this moment. In general, the types emerge are caused effect economy and spesific education and inhabitant mobility.